Stenorynchoacrum xijiangensis, a new genus and a new species of Labeoninae fish from Guangxi, China (Teleostei: Cyprinidae - Huang, Yanfei; Yang, Junxing; Chen, Xiaoyong (Zootaxa, 2014)
Stenorynchoacrum xijiangensis, a new genus and a new species of Cyprinidae, is described from a tributary of the Zhujiang River (Pearl River) in Guangxi Province, China. It can be distinguished from other genera of Labeoninae by the following characters: middle part of rostral cap undeveloped, narrow, only covering the base of the upper jaw, both sides of rostral cap well developed and extending upward, rostral cap connected the lower lip with free lateral margin, the median part of lower lip protruded to form a round fleshy pad, whose posterior margin continuous with the mental region.